ANALISIS KUALITAS PRODUK, HARGA, DAN PROMOSI SEBAGAI UPAYA MENSTIMULUS KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK MINYAK GORENG SOVIA DI ALFAMART GONDANG NGANJUK - Mayangsari, Hesti; Ichsannudin, Ichsannudin; Kurniawan, Rony (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2022)
To determine whether a company is making progress toward its current and future goals, it is important to analyze the factor is that influence purchasing decisions. This study aims to determine the partial and simultaneous significance of Product Quality, Price, and Promotion on consumers of Sovia cooking oil at Alfamart Gondang Nganjuk. The research data of this research are numbers that are described quantitatively and analyzed statistically at the technical level. Questionnaires were used to collect data on this investigation. The research sample of 54 participants was analyzed using multiple linear regression, hypothesis testing, and analysis of the coefficient of determination using SPSS for Windows version 23 software (R2). Based on the results of the calculated F test of 17.681 and a significance level of 0.000<0.05, the conclusion of the study is that product quality, price, and promotion have a significant effect on consumer purchasing decisions for Sovia cooking oil product. at Alfamart Gondang Nganjuk.